Systematics review: effect ethanol to dna methylation - Putri, Nugrah Utama; Tualeka, Abdul Rohim; Ardyanto, Denny Y.; Affilin, Aisyah Aulyanti; Jalaludin, Juliana; Russeng, Syamsiar S.; Ahsan; Rahmawati, Pudji (ASR Research India, 2022)
Aims: The purpose of writing a literature review is to determine the relationship between the effects of ethanol exposure on DNA methylation in embryos. Methods: (1) The inclusion criteria used were free full text, without comparison, Outcomes: DNA Methylation, research articles, published between 2012-2022, and using English. While the exclusion criteria used were abstract, there were comparisons, not research articles, and did not use English. (2) The data source comes from PubMed, writing this literature review begins on May 16, 2022. Results: Total data based on searches using the keywords "Ethanol" AND "DNA Methylation" (n=278), focusing on embryos (n=13), research articles and free full text (n=8), and inclusion criteria (n=5). Discussion: (1) There is a relationship between the effect of ethanol exposure on DNA methylation in embryos. (2) There is limited evidence so that original research research on the subject is needed. Conclusions: (1) There is a relationship between the effect of ethanol exposure on DNA methylation in embryos. (2) Exposure to ethanol affects gene expression changes in the hippocampus, bone marrow, and major olfactory epithelium. (3) The effects of ethanol can be reduced by taking betaine supplements.